Non-Arrhenius behaviour of nickel self-diffusion in liquid Ni77Si23. (28th September 2022) - Demmel, F
Abstract: Nickel self-diffusion was measured for a Ni77 Si23 alloy in the liquid state over a temperature range of about 400 K through quasielastic neutron scattering. At the two lowest temperature points the derived diffusion coefficients deviate from a high-temperature Arrhenius-type behaviour and indicate a change in dynamics above the liquidus temperature. A fit with a power-law temperature dependence as predicted by the mode coupling theory for the liquid to glass transition can describe the diffusion coefficients quite well over the whole measured temperature range. The obtained results agree with predictions from a classical molecular dynamics (MD)-simulation, which evidenced an increasing glass forming ability with increasing silicon content. A crossover to a super-Arrhenius behaviour was reported for metallic glass formers above the liquidus temperature and the here investigated NiSi alloy demonstrates the same signature.